The Effect of Chronic Psychological Stress on Lower Urinary Tract Function: An Animal Model Perspective - Gao, Yunliang; Rodríguez, Larissa V. (Frontiers in Physiology, 2022)
Chronic psychological stress can affect urinary function and exacerbate lower urinary tract (LUT) dysfunction (LUTD), particularly in patients with overactive bladder (OAB) or interstitial cystitis–bladder pain syndrome (IC/BPS). An increasing amount of evidence has highlighted the close relationship between chronic stress and LUTD, while the exact mechanisms underlying it remain unknown. The application of stress-related animal models has provided powerful tools to explore the effect of chronic stress on LUT function. We systematically reviewed recent findings and identified stress-related animal models. Among them, the most widely used was water avoidance stress (WAS), followed by social stress, early life stress (ELS), repeated variable stress (RVS), chronic variable stress (CVS), intermittent restraint stress (IRS), and others. Different types of chronic stress condition the induction of relatively distinguished changes at multiple levels of the micturition pathway. The voiding phenotypes, underlying mechanisms, and possible treatments of stress-induced LUTD were discussed together. The advantages and disadvantages of each stress-related animal model were also summarized to determine the better choice. Through the present review, we hope to expand the current knowledge of the pathophysiological basis of stress-induced LUTD and inspire robust therapies with better outcomes.